2009
DOI: 10.1001/archsurg.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Actual 3-Year Survival After Laparoscopy-Assisted Gastrectomy for Gastric Cancer

Abstract: Laparoscopy-assisted gastrectomy is acceptable oncologically in early gastric cancer if 3-year disease-free survival represents 5-year overall survival. Laparoscopy-assisted gastrectomy may also play an important role in the treatment of advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 45 publications
2
33
0
3
Order By: Relevance
“…Laparoscopic gastrectomy is an alternative option for the treatment of early gastric cancer, and is associated with less postoperative pain, a shorter recovery period after surgery, and fewer complications [8][9][10][11]. Recent studies suggested that the indications for this procedure be extended from locally-advanced cancer to far-advanced cancer to reflect the advances made in laparoscopic devices and techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic gastrectomy is an alternative option for the treatment of early gastric cancer, and is associated with less postoperative pain, a shorter recovery period after surgery, and fewer complications [8][9][10][11]. Recent studies suggested that the indications for this procedure be extended from locally-advanced cancer to far-advanced cancer to reflect the advances made in laparoscopic devices and techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As a minimally invasive surgery, laparoscopic gastrectomy has several advantages over open gastrectomy, especially with respect to early postoperative outcomesthat is, it reduces postoperative pain, surgical stress, and estimated blood loss, it accelerates recovery and return to normal bowel function and oral intake, and it reduces the duration of hospital stay [6][7][8][9]. Because gastric cancer is mostly located in the distal area in patients in Eastern countries, laparoscopic distal gastrectomy has been a more common procedure than laparoscopic total or proximal gastrectomy.…”
mentioning
confidence: 99%
“…A large number of surgeries involving gastrectomy with standard lymph node dissection have been carried out in South Korea and Japan (8,9). The results of randomized research allow us to conclude that gastrectomy has a number of advantages over conventional surgery; these are less blood loss and fewer complications, quicker patient recovery, fewer post-operative bed days, better visual effects, and almost the same 5-year survival rates at 57.3% vs. 58.9% (10)(11)(12).…”
Section: Minimally Invasive Treatment For Early Gcmentioning
confidence: 99%